Effect of Calcination Temperature of Musa sapientum Linn Peels as a Novel Biobased Heterogeneous Catalyst for Soybean Oil-derived Fatty Acid Methyl Ester Formation - Jakkrapong Jitjamnong (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science